DAMPAK PELAKSANAAN KEGIATAN EKSTRAKURIKULER SENI TARI DI SMP NEGERI 5 KERINCI - Malani, Lusi; Asriati, Afifah; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
Abstract This article aims to describe the Impact of the implementation of extracurricular activity in dancing at SMP Negeri 5 Kerinci . The type of research was qualitative research with using descriptive method. The object of research was the students of class VIII and the researcher. Techniques of data collection were done by using library research, observation, interviews and documentation. Meanwhile, Techniques of data analysis were done by  collecting, identifying and analyzing data. The result shows that the students who get the highest score (Very Good) are included in participating on the FLS2N competition in Kerinci Regency appropriate with the direction of the headmaster of SMP Negeri 5 Kerinci .The headmaster gives his appreciation to all school parties who have contributed and participated in reviving extracurricular activity at SMP Negeri 5 Kerinci especially to students delegation, Amir S. because by holding the extracurricular activity in 2019, SMP Negeri 5 Kerinci sends delegation to participate on district level. It is different from the previous year, SMP Negeri 5 Kerinci do not participate in the FLS2N competition. It indicates that SMP Negeri 5 Kerinci  has progressed. Keywords: Implementation, Extracurricular, Dance.